2021
DOI: 10.1155/2021/3401654
|View full text |Cite|
|
Sign up to set email alerts
|

κ-Opioid Receptor Agonist Ameliorates Postoperative Neurocognitive Disorder by Activating the Ca2+/CaMKII/CREB Pathway

Abstract: Objective. Cardiopulmonary bypass (CPB) is an important cardiac operation and also a high-risk procedure, leading to postoperative neurocognitive disorder. However, there are few effective drugs to treat the aftermath of CPB. Therefore, we observe the effect of kappa opioid receptor (KOR) agonist on cognitive disorders of rats after cardiopulmonary bypass (CPB) and investigate the mechanism of the Ca2+/calmodulin-dependent protein kinase (CaMKII)/cAMP responsive element-binding protein (CREB) pathway. Methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…administration of U50,488 or the KOR peptide dynorphin A, reduced cognitive dysfunction in mice that had undergone excision of the olfactory bulb. Furthermore, Fan et al (2021) , Ding et al (2021) , and Li et al (2019) all found that U50,488 mitigated postoperative cognitive dysfunction in rats that underwent cardiopulmonary bypass. Fan et al (2021) also reported that U50,488 reduced hippocampal damage, inhibited the rate of neuronal apoptosis, and promoted recovery from oxidative stress–induced injury.…”
Section: Diseases For Which the Kappa-opioid Receptors Has Therapeuti...mentioning
confidence: 93%
“…administration of U50,488 or the KOR peptide dynorphin A, reduced cognitive dysfunction in mice that had undergone excision of the olfactory bulb. Furthermore, Fan et al (2021) , Ding et al (2021) , and Li et al (2019) all found that U50,488 mitigated postoperative cognitive dysfunction in rats that underwent cardiopulmonary bypass. Fan et al (2021) also reported that U50,488 reduced hippocampal damage, inhibited the rate of neuronal apoptosis, and promoted recovery from oxidative stress–induced injury.…”
Section: Diseases For Which the Kappa-opioid Receptors Has Therapeuti...mentioning
confidence: 93%
“…В исследованиях было обнаружено, что каппаопиоидный агонист U50,488H снижает сывороточные уровни TNF-α, IL-1β и IL-6, подавляет экспрессию NF-κB в гиппокампе, а также скорость апоптоза нейронов гиппокампа у крыс посредством активации КОР, что служит свидетельством его эффективности в отношении борьбы с оксидативным стрессом и нейровоспалением [83]. Указанные цитокины могут быть использованы в качестве маркеров при изучении каппа-опиоидных лигандов в модели нейровоспаления, индуцированного ОК.…”
Section: нейровоспаление индуцированное окадаевой кислотойunclassified
“…Journal of Healthcare Engineering has retracted the article titled “ κ -Opioid Receptor Agonist Ameliorates Postoperative Neurocognitive Disorder by Activating the Ca 2+ /CaMKII/CREB Pathway” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled "κ-Opioid Receptor Agonist Ameliorates Postoperative Neurocognitive Disorder by Activating the Ca 2+ / CaMKII/CREB Pathway" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%